2006
DOI: 10.2215/cjn.01461005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ANCA-Associated Primary Renal Vasculitis in the Miyazaki Prefecture

Abstract: There were no WG or CSS patients. The incidence of PRV did not differ between Japan and Europe, but WG was not widespread in Japan. Furthermore, the ratio of serum MPO to PR3-ANCA among Japanese with PRV was much higher than that found among European and US patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 30 publications
8
55
1
Order By: Relevance
“…The geographical studies of AAV indicated the predominance of MPA and MPO-ANCA positivity as epidemiologically specific to Japan, whereas GPA and PR3-ANCA positivities are dominant in European countries. 9,[17][18][19] According to the results in the present study, this Japanese specificity is consistent with the epidemiology of patients without HP; however, the epidemiology of patients with HP is similar to that of patients in European countries. With regard to the pattern of ANCA positivity, frequency of PR3-ANCA was equal to that of MPO-ANCA in patients with HP, although the predominance of MPO-ANCA has been demonstrated in the Japanese population with GPA.…”
Section: Discussionsupporting
confidence: 88%
“…The geographical studies of AAV indicated the predominance of MPA and MPO-ANCA positivity as epidemiologically specific to Japan, whereas GPA and PR3-ANCA positivities are dominant in European countries. 9,[17][18][19] According to the results in the present study, this Japanese specificity is consistent with the epidemiology of patients without HP; however, the epidemiology of patients with HP is similar to that of patients in European countries. With regard to the pattern of ANCA positivity, frequency of PR3-ANCA was equal to that of MPO-ANCA in patients with HP, although the predominance of MPO-ANCA has been demonstrated in the Japanese population with GPA.…”
Section: Discussionsupporting
confidence: 88%
“…Three other studies did give rise to some concerns: the study from Lithuania (33) was hospital based and may have missed community cases, the diagnostic criteria used by Zeft et al (34) were not stated in their abstract, and the study from Japan (35) was based on referral to a renal unit and may have missed those with nonrenal disease. However, the denominator population in this case was clearly defined (35), and other sources (36) attest to the rarity of WG in this region. We extracted the number of cases of each disease entity, noting the location, year of publication, and the source population, e.g., general, adult-only.…”
Section: Methodsmentioning
confidence: 66%
“…Conceivably, the very low reported incidence of WG in Kuwait (30), Japan (35), and Lima, Peru (61) could be caused by differences in genetic susceptibility of the underlying populations. Nevertheless, a prevalence survey within a relatively genetically homogeneous population, the New Zealand European population, provides supportive evidence for a latitudinal gradient in WG that is not confounded by variation in ethnicity (8).…”
Section: Association Between Uv Radiation and Wg Mpa And Cssmentioning
confidence: 99%
“…AAV is classified into four types according to clinical symptoms, clinical presentation, and laboratory findings: eosinophilic granulomatosis with polyangiitis (EGPA), granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and polyarteritis nodosa (PAN) (Jennette et al 1994;Wiik 2002;Jennette et al 2013). Among these types of AAV, the incidence of MPA is higher in Japan than it is in the US and Europe (Fujimoto et al 2006(Fujimoto et al , 2011Shiraki et al 2007;Watts et al 2008). The effects of AAV are often restricted to small-and medium-sized vessels, resulting in kidney and lung pathologies in patients with MPA.…”
Section: Introductionmentioning
confidence: 99%